1981
DOI: 10.1002/pol.1981.170190101
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric porous emulsion film

Abstract: The formation mechanism of an “asymmetric” porous structure for the film cast from ethyl acrylate‐methyl methacrylate copolymer emulsion prepared by emulsifire‐free emulsion polymerization was investigated. The formation of this structure was affected by the emulsion stability which was varied by the postaddition of sodium sulfate or sodium dodecyl benzene sulfonate. It is concluded that it is derived from the production of porous skin film at the emulsion‐air interface and the precipitation of flocculated par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…During film formation, the outer clear region increases at the expense of the central turbid, wet region. Okubo et al (3) studied the same three regions, and they also reported that a thin film-formed layer or "skin" existed on the surface of the central wet region. This skin is indicative of a drying and coalescence front normal to the latex surface.…”
mentioning
confidence: 93%
“…During film formation, the outer clear region increases at the expense of the central turbid, wet region. Okubo et al (3) studied the same three regions, and they also reported that a thin film-formed layer or "skin" existed on the surface of the central wet region. This skin is indicative of a drying and coalescence front normal to the latex surface.…”
mentioning
confidence: 93%
“…5, top). Other authors 24,25 have also observed outer rings, and they associated them with a high density of flocculated particles. They supported this by rinsing the drying films with water: only the unflocculated particles were dragged.…”
Section: DLmentioning
confidence: 90%
“…38 -44 Okubo et al 45 also showed that ethyl acrylate/methyl methacrylate copolymer latex films decreased in permeability as the sodium dodecyl benzene sulfonate (SDBS) concentration was increased. The reduction of permeability of latex films may be a result of morphological changes in the film because the addition of a hydrophilic surfactant is expected to increase permeability.…”
Section: Surfactant Behavior In Latex Filmsmentioning
confidence: 94%